Attentional Engagement as Practice: A Study of the Attentional Infrastructure of Healthcare Chief Executive Officers - Nicolini, Davide; Korica, Maja (Organization Science, 2021)
In this paper, we investigate the attentional engagement of chief executive officers (CEOs) of large healthcare organizations in England. We study attention ethnographically as something managers do—at different times, in context, and in relation to others. We find that CEOs match the challenges of volume, fragmentation, and variety of attentional demands with a bundle of practices to activate attention, regulate the quantity and quality of information, stay focused over time, and prioritize attention. We call this bundle of practices the CEO’s attentional infrastructure. The practices that compose the attentional infrastructure work together to ensure that CEOs balance paying too much with paying too little attention, sustain attention on multiple issues over time, and allocate attention to the issues that matter, while avoiding becoming swamped by too many other concerns. The attentional infrastructure and its component practices are constantly revised and adapted to match the changes in the environment and ensure that managers remain on top of the things that matter to them. The idea of a practice-based attentional infrastructure advances theory by expanding and articulating the concept of attentional engagement, a central element in the attention-based view of the firm. We also demonstrate the benefits of studying attention as practice, rather than as an exclusively mental phenomenon. Finally, we contribute to managerial practice by introducing a set of categories that managers can use to interrogate their existing attentional practices and address attentional traps and difficulties.